Toward a conceptualization of giftedness in the Philippine context - Baldo, Trinidad C.
This study attempted to determine Filipino conceptualizations of giftedness among selected groups of respondents and the utilization of these concepts at home and in school.
Keywords: Gifted persons -- Philippines; Gifted children -- Identification